Förutsättningar för förståelse: Läsning av musikkritik under mellankrigstiden i Göteborg - Edström, Olle (Svensk tidskrift för musikforskning / Swedish Journal of Music Research, 1994)
This article aims to discuss point of departure and possibilities for music criticism in Göteborg during the interwar period, especially the work of critic Julius Rabe. The author starts out from his earlier discussion on middle music as the music of the boureoisie (STM 1989, 1992:1). Julius Rabe took on the resposibility for music criticism in in the well respected newspaper Göteborgs Handels- och Sjöfartstidning (GHT) in 1918. Rabe had studied piano and music theory in Stockholm and studied musicology during a five year stay i Germany (1912–1917). He was the first critic in Göteborg to take up the role of German music critics. It soon was clear to GHT’s readers that Rabe accepted operettas, liked classical and romantic chamber music, but was sceptical to works with programmatic titles. His ideal was Carl Nielsen. Only a small part of GHT’s readers could follow Rabe’s way of reasoning and understand his language when he wrote on an abstract level. The readers built an understanding of Rabe’s ideas by learning which composers he liked. The more distanced the reader was from the underlying values of the bourgois music culture , the less prepared he or she was to fully understand Rabe’s writing. The popularity of middle music and the art music that was stylistically close to the middle music did not decrease during the interwar years. The appreciation of modern contemporary art music, which seldom is performed, during this period, decreases. Modern contemporary art music is performed more frequently after World War II. Seen from a broader perspective (from early 1900th century to present time), the role of the critic has changed and can be dividen into three periods: a) the critic represents the taste of the audience, b) the critic becomes an explainer and interpreter, and c) the critic becomes a defender of the latest achievements in art music. The more the critics supported and followed the composers, the more they lost contact with and understanding of how most people played and listened to middle music and pop.